2001
DOI: 10.1116/1.1412654
|View full text |Cite
|
Sign up to set email alerts
|

Micromachined piezoresistive cantilever array with integrated resistive microheater for calorimetry and mass detection

Abstract: We describe a microcantilever calorimeter consisting of an array of ten cantilevers. Each single cantilever is capable of detecting heat energy with the resolution of 50 nW Hz (Ϫ0.5) . The device is based on a Si microcantilever coated with a 1 m thick layer of SiO 2 deposited with a 700 nm thick layer of aluminum which forms a resistive microheater. Heat fluxes are monitored by detecting the cantilever deflection ͑bending͒ due to the bimaterial structure of the cantilever ͑dissimilar thermal expansion proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(36 citation statements)
references
References 6 publications
0
36
0
Order By: Relevance
“…It has its own advantages and disadvantages in fabrication process. For the realization of suspended/freestanding microstructures made of materials such as p + -Si, SiO 2 , Si 3 N 4, etc., silicon beneath a structural component needs to be removed [1][2][3][4][5]10,70,[161][162][163]. If the process is done only on one side of the wafer, the removal of underneath material is only possible by undercutting process [70,161,162].…”
Section: Advantages and Disadvantages Of Corner Undercuttingmentioning
confidence: 99%
“…It has its own advantages and disadvantages in fabrication process. For the realization of suspended/freestanding microstructures made of materials such as p + -Si, SiO 2 , Si 3 N 4, etc., silicon beneath a structural component needs to be removed [1][2][3][4][5]10,70,[161][162][163]. If the process is done only on one side of the wafer, the removal of underneath material is only possible by undercutting process [70,161,162].…”
Section: Advantages and Disadvantages Of Corner Undercuttingmentioning
confidence: 99%
“…We observed that the dynamic behaviour of the sensor is a function of relative humidity change. 21,24 The mass of the adsorbed vapour after moistening, respectively. The system can also be used as ''electronic nose''.…”
Section: Cantilever Microbalancementioning
confidence: 99%
“…It has its own advantages and disadvantages in fabrication process. For the realization of suspended/freestanding microstructures made of materials such as p+-Si, SiO2, Si3N4, etc., silicon beneath a structural component needs to be removed [1][2][3][4][5]10,70,[161][162][163]. If the process is done only on one side of the wafer, the removal of underneath material is only possible by undercutting process [70,161,162].…”
Section: Advantages and Disadvantages Of Corner Undercuttingmentioning
confidence: 99%